Kajian Penambahan Exercise Local Flight Pada Mata Kuliah Praktik Approach and Area Control Program Studi Diploma III Lalu Lintas Udara di Politeknik Penerbangan Makassar - Supardam, Dhian (Politeknik Penerbangan Makassar, 2020)
This study aims to determine whether additional local flight exercise is required in the practical subject of Approach and Area Control Diploma III Air Traffic (D-III LLU) at the Makassar Aviation Polytechnic. This study involved a sample of 10 lecturers and 47 cadets of LLU D-III by using 4 (four) data collection techniques, namely: observation, survey, interview, and questionnaire. The data analysis technique used in this research is descriptive qualitative. The results of this study are: (1) In the practical course of Approach and Area Control, there is no traffic in the form of local flights because they are not listed in the curriculum given; (2) Lecturers and cadets hope that there will be additional local flight exercises in the Approach and Area Control practical course in order to add insight and equip Taruna / i to real conditions in the field; and (3) the addition of local flight exercises in the Approach and Area Control practical course in the Air Traffic D-III Study Program needs to be followed up with curriculum standardization.